ANALISIS INFORMASI LABA AKUNTANSI DAN ARUS KAS TERHADAP HARGA SAHAM (STUDI EMPIRIS PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2018) - Parso Parso (Institut Teknologi dan Bisnis Swadharma, 2020)
The purpose of this study was to determine the analysis of accounting earnings and cash flow information on stock prices in the manufacturing sector food and beverage subsector consumption sector listed on the Indonesia Stock Exchange both partially and simultancously. The research method used in this study is quantitative research with descriptive design. Data collection was carried out by library research on some literature and downloading from setus www.idx.co.id. The population in this study were 17 companies of consumer goods industries which were found in the Indonesian Stock Exchange from 2014-2018 What is done using the withdrawal technique to stabilize desgn samples is to use pusposive sepling. Based on the sampling technique above, what will become the sample in this study are 4 manufacturing companies in the consumer goods industry. The research data were processed by statistical analysis with tests of normality, multicollinearity, heterosecadity, autocorrelation, multiple linear regression hypothesis testing, t test, f test, and the coefficient of determination. The results of this study indicate that accounting earnings and cash flow information has a positive effect on stock prices, adjusted R-Squere value of 0.564. This shows that the independent variable accounting income and cash flow is able to explain the dependent variable (stock price) of 56.4% and the remaining 43.6% is explained by other variables for example: financial performance, overall, political concessions, natural conditions, security conditions, Countries, etc.) not examined in this study.